Contemporary Approaches to the Quality of Life: from Objective Contexts to Subjective Ones - Lebedeva, A.A.; Leontiev, D.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2022)
Objective. Quality of life is a category that develops in breadth, but not in depth. The objective of the paper is a brief systematic presentation of the approaches of three influential representatives of a field of interdisciplinary research of the quality of life, who contributed a lot to the shaping of this field and its development till our days, namely Alex Michalos, Joseph Sirgy and Ruut Veenhoven. Background. These three concepts of quality of life may be viewed as representing the main trend in quality of life research has evolved through the last three decades. The essential characteristics of this trend are, first of all, growing interdisciplinarity of both theoretical models and empirical research of the quality of life, increasing contribution of psychology to the understanding and investigating this area and progressing shift of the focus of research from objective living conditions to the subjective indicators of quality of life. Methodology. A transdisciplinary comparative analysis. Conclusions. These closely interconnected characteristics bridge quality of life studies focused on the specifics of different types of societies and cultures with the research of happiness and subjective well-being at an individual psychological level. The positive psychology currently defines today the main stream of understanding the quality of life in interdisciplinary research. This trend is expected to develop in direction increasing attention to the socio-psychological features of the personality, which determine its quality of life. Цель. Качество жизни - категория, которая развивается вширь, но не вглубь. Цель данной статьи - системное изложение взглядов трех авторитетных представителей области междисциплинарных исследований качества жизни, внесших большой вклад в становление этой области и развитие ее до наших дней: А. Майкалоса, Дж. Сирджи и Р. Винховена. Контекст и актуальность. Три концепции качества жизни выражают собой общий тренд, по которому развиваются исследования качества жизни в последние три десятилетия. В качестве содержательных характеристик этого тренда отмечаются: растущая междисциплинарность теоретических моделей и эмпирических исследований качества жизни, увеличивающийся вклад со стороны психологии в понимание и изучение этой области, смещение внимания исследований с объективных характеристик условий жизни на субъективные индикаторы качества жизни. Используемая методология: трансдисциплинарный сравнительный анализ. Основные выводы. Взаимосвязанные между собой оценки счастья, удовлетворенности и субъективного благополучия перебрасывают мост между исследованиями, в центре которых находится специфика разных типов обществ и культур, и исследованиями качества жизни на индивидуально-психологическом уровне. Позитивная психология определяет на сегодняшний день ключевой вектор понимания качества жизни в междисциплинарных исследованиях. Ожидается, что эта тенденция получит свое развитие в направлении роста интереса к тому, как социально-психологические особенности личности определяют качество жизни.